Utility of Exfoliative Cytology of Voided Urine in Comparison with Ultrasonogram and Cystoscopy Findings in the Diagnosis of Urothelial Cancers - Badruddoza, SM; Azim, FA; Rahman, AJE Nahar; Kamal, M; Barua, AR; Khan, KH; Chowdhury, T (TAJ: Journal of Teachers Association, 2018)
Carcinoma of the urinary bladder affects men more often than women and occurs in patients over the age of 50 years. Transitional cell carcinoma (TCC) comprises about 90% of all primary tumor of urinary bladder. In this study a total of 57 cases were taken. The aim of the study was to establish diagnostic role of voided urine cytology, ultrasonography and cystoscopy in urothelial cancers. Out of 57 cases, cytological diagnosis was positive in 53 cases (93%) and negative in 4 cases (7%). There were no atypical or suspicious cases. Of the total cases, cytology was negative only in 7% cases. Among 42 invasive carcinomas 14 (33%) grade III invasive flat carcinoma, one (2%) invasive papillary adenocarcinoma and two (5%) invasive squamous cell carcinoma, each of them gave 100% positive cytology. Of the remaining 25 (60%) invasive papillary TCC, 21 were in grade II and 4 were in grade III. They gave 90% and 100% positive cytologic results. Ultrasonogram of urinary bladder gave 95% (approx.) positive results and out of 57 cases, 3 cases failed to give positive results in ultrasonogram (USG) of the urinary tract. Cystoscopy detected tumor mass in 98% cases and it gave false negative result in 2% cases. Fifty-two tumors had a diameter ranging 1.1- 6 cm. Single lesions were seen in 40 cases, double lesion in one case and multiple in 13 cases. The probability of later invasive carcinomas nearly tripled in-patients with multiple lesions on presentation (13.6%) compared with those who presented with a single lesion (4.6%). Consistent with previously published data, this study showed the highest diagnostic accuracy with high-grade tumors and lowest with low-grade tumors. So in a proper clinical setting, non-invasive technique like voided urine cytology and ultrasonography could be done as a first line cost effective method in the diagnosis of urothelial cancers. TAJ 2017; 30(2): 39-46